Effect of the combination of 25-hydroxyvitamin D3 and higher level of calcium and phosphorus in the diets on bone 3D structural development in pullets - White, Dima; Chen, Chongxiao; Kim, Woo Kyun (Frontiers in Physiology, 2023)
Bone issues such as osteoporosis are major concerns for the laying hen industry. A study was conducted to improve bone-health in pullets. A total of 448 one-day-old Hyline W36 pullets were randomly assigned to four treatments (8 rep;14 birds/rep) until 17 weeks (wks). Dietary treatments were: 1) vitamin D3 at (2,760IU/kg) (D), 2) vitamin D3 (2,760IU/kg)+62.5mg 25-(OH)D3/ton (H25D), 3) vitamin D3 (2,760IU/kg) + 62.5mg 25-(OH)D3/ton + high Ca&P (H25D+Ca/P), and 4) vitamin D3 (2,760IU/kg) + high Ca&P (D+Ca/P). The high calcium (Ca) and phosphorus (P) diet was modified by increasing both Ca & P by 30% (2:1) for the first 12wks and then only increasing P for 12-17wks to reduce the Ca to P ratio. At 17wk, growth performance was measured, whole body composition was measured by dual energy x-ray absorptiometry (DEXA), and femur bones were scanned using Micro-computed tomography (Micro-CT) for bone 3D structure analyses. The data were subjected to a one-way ANOVA using the GLM procedure, with means deemed significant at P<0.05. There was no significant outcome for growth performance or DEXA parameters. Micro-CT results indicated that the H25D+Ca/P treatment had lower open pore volume space, open porosity, total volume of pore space, and total porosity in the cortical bone compared to the D+Ca/P. It also showed that a higher cortical bone volume/tissue volume (BV/TV) in the H25D+Ca/P than in the D+Ca/P. Furthermore, the H25D+Ca/P treatment had the lowest trabecular pattern factor and structure model index compared to the other treatments, which indicates its beneficial effects on trabecular structural development. Moreover, the H25D+Ca/P had a higher trabecular percentage compared to the D and 25D, which suggests the additional Ca & P supplementation on topon top of 25D increased trabecular content in the cavity. In conclusion, the combination of 25D with higher levels of Ca & P could improve cortical bone quality in pullets and showed a beneficial effect on trabecular bone 3D structural development. Thus, combination of a higher bio-active form of vitamin D3 and higher levels of Ca & P could become a potential feeding strategy to improve bone structural integrity and health in pullets.